2017
DOI: 10.18632/oncotarget.20344
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of preoperative inflammatory response biomarkers for metabolic syndrome and post-PCNL systemic inflammatory response syndrome in patients with nephrolithiasis

Abstract: Neutrophil to lymphocyte ratio (NLR), derived neutrophil to lymphocyte ratio (dNLR), platelet to lymphocyte ratio (PLR) and lymphocyte to monocyte ratio (LMR) were promising biomarkers used to predict diagnosis and prognosis in various inflammatory responses diseases and cancers. However, there have been no reports regarding these biomarkers in kidney stone patients. This study aimed to evaluate the predictive value of inflammatory biomarkers for metabolic syndrome (MetS) and post-PCNL SIRS in nephrolithiasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 40 publications
(40 reference statements)
3
46
0
Order By: Relevance
“…In a retrospective study of 513 patients with nephrolithiasis and 204 healthy controls, a signi cant difference was obtained in NLR, dNLR, and LMR between the patients with nephrolithiasis and healthy controls [(2.3 vs. 1.6; P < 0.001), (1.6 vs. 1.2; P < 0.001), (4.2 vs. 5.0; P < 0.001) respectively], whereas the PLR levels were comparable between both the groups (122.9 and 126.4). Signi cantly lowered levels of LMR was observed in patients with kidney stone [5]. In the present study, the lymphocyte level was signi cantly lower, while RDW level was signi cantly higher in patients with kidney stones.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…In a retrospective study of 513 patients with nephrolithiasis and 204 healthy controls, a signi cant difference was obtained in NLR, dNLR, and LMR between the patients with nephrolithiasis and healthy controls [(2.3 vs. 1.6; P < 0.001), (1.6 vs. 1.2; P < 0.001), (4.2 vs. 5.0; P < 0.001) respectively], whereas the PLR levels were comparable between both the groups (122.9 and 126.4). Signi cantly lowered levels of LMR was observed in patients with kidney stone [5]. In the present study, the lymphocyte level was signi cantly lower, while RDW level was signi cantly higher in patients with kidney stones.…”
Section: Discussionsupporting
confidence: 44%
“…Extensive literature search revealed that there is limited studies reported association of elevated in ammatory biomarkers in patients with urolithiasis [5]. Therefore, present study aimed to compare association of in ammatory biomarkers with urolithiasis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Atherosclerosis in humans is induced by various components of MetS, and when these components occur together, they are more significant in promoting atherosclerosis [6, 7]. Therefore, in both developed and developing countries, MetS is a fairly serious public health problem [810]. It is thus important to improve the preventive and therapeutic strategies of MetS.…”
Section: Introductionmentioning
confidence: 99%
“…In multivariate analysis, this is only valid for age, platelet count and white blood cell count. Upon a look into the literature, Tang et al(20) emphasized that NLR ratio was an independent factor in predicting post-PCNL Systemic Inflammatory Response syndrome. Similar to our study, Cetinkaya et al(21) indicated that NLR was important in predicting post-PCNL fever in univariate analysis, but not in multivariate analysis.…”
mentioning
confidence: 99%